2013
DOI: 10.1590/s1983-14472013000400018
|View full text |Cite
|
Sign up to set email alerts
|

Resultados de enfermagem para padrão respiratório ineficaz e ventilação espontânea prejudicada em terapia intensiva

Abstract: This study aimed to validate the results of Nursing selected from the link NANDA-I-NOC (Nursing Outcomes Classification--NANDA--International) for diagnosis Ineffective Breathing Pattern and Impaired Spontaneous Ventilation in adult intensive care unit. This is a content validation study conducted in a university hospital in southern Brazil with 15 expert nurses with clinical experience and knowledge of the ratings. The instruments contained five-point Likert scales to rate the importance of each outcome (1st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
2
Order By: Relevance
“…The nurses of a university hospital judged each outcome and its indicators in relation to their importance for each of the two diagnoses. It was concluded that the NOC is valid in the studied context and presents the elements that nurses need to assess patients during their daily care routine (25) . The content of four nursing outcomes -Self-care: Activities of Daily Living (ADL), Self-care: Bathing, Self-care: Hygiene and Self-care: Oral Hygiene, related to the diagnosis "Self-care defi cit: bathing/toileting" presented by Brazilian patients in postoperative orthopedic care, were also validated by 37 nurses (26) .…”
Section: Validation Of Nursing Outcomesmentioning
confidence: 95%
“…The nurses of a university hospital judged each outcome and its indicators in relation to their importance for each of the two diagnoses. It was concluded that the NOC is valid in the studied context and presents the elements that nurses need to assess patients during their daily care routine (25) . The content of four nursing outcomes -Self-care: Activities of Daily Living (ADL), Self-care: Bathing, Self-care: Hygiene and Self-care: Oral Hygiene, related to the diagnosis "Self-care defi cit: bathing/toileting" presented by Brazilian patients in postoperative orthopedic care, were also validated by 37 nurses (26) .…”
Section: Validation Of Nursing Outcomesmentioning
confidence: 95%
“…Other factors that may contribute to the onset of fatigue are age and number of comorbidities 17 . Regarding the number of morbidities, studies have shown an association between greater number of morbidities and greater perception of fatigue 28-29 .…”
Section: Discussionmentioning
confidence: 99%
“…Anginal pain triggers manifestations of the sympathetic system that cause an increase in heart rate and breathing, altering the breathing mechanics regarding depth, number of incursions per minute. Without intervention, this will lead to respiratory muscle fatigue and consequent IBP diagnosis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In the implementation of the nursing process, the results are closely linked to NANDA-I nursing diagnoses. The link between NANDA-I and NOC taxonomies suggests a relationship between the problems identified as real or potential in the patient and the responses that are expected to be achieved through care actions (12) . Thus, the NOC taxonomy can be used in conjunction with NANDA-I diagnoses in nursing care planning so that the process of caring for the patients in the postoperative period is based on their needs.…”
Section: Introductionmentioning
confidence: 99%